Using dimpled-pipe surface to reduce submarine landslide impact forces on pipelines at different span heights. (15th January 2022) - Guo, Xingsen; Nian, Tingkai; Stoesser, Thorsten
Abstract: The interaction between submarine landslides and pipelines has attracted widespread attention. For a pipeline designer, generalizing practical analysis models, obtaining accurate dynamic forces (i.e., the drag force and lift force), and proposing effective pipeline protection measures are prerequisites for ensuring their safe operation. In this paper, a computational fluid dynamics approach is employed to investigate if a golfball-type dimpled pipeline surface reduces impact forces induced by submarine landslides. Considering technology suspension, geomorphology suspension, environmental erosion suspension and acquired suspension, numerical models are generalized to allow prescribing different pipeline span heights, and are impacted by fluidized homogeneous submarine landslides. For the given Reynolds numbers and span heights, golfball-type dimpled pipelines experience a reduced peak drag force than standard circular pipelines. In addition, the pipeline dimple suppresses the lift force variation and greatly reduces the force amplitude. As a result, pipeline damage could be lessened or even avoided. Also, a methodology for predicting the drag reduction of dimple-surfaced pipelines under various conditions is provided, and the two necessary conditions for the periodic vibration of the lift force are proposed. Finally, the full life cycle of vortices shed from the pipeline and the hydrodynamics during landslides impact on pipelines are revealed providing the needed insights to prevent future submarine pipeline failures. Highlights: Computational Fluid Dynamics simulations shed light on the complex submarine-landslide-pipeline interaction under complex and variable subsea conditions. The characteristics of peak dynamic forces (i.e., drag and lift forces) of submarine landslide-pipeline interaction as a function of Reynolds number and pipeline span height are systematically given. Two necessary conditions for the periodic vibration of the lift force acting on submarine pipelines are proposed. A methodology for predicting the drag reduction of golfball-type dimpled pipeline under various scenarios is established. Based on the velocity field evolution, boundary layer and vortex development theories, the drag reduction mechanism of dimpled pipelines with different span heights is discussed.